The dirty streets of heaven - Williams, Tad (Williams, Tad. Bobby Dollar novel., 2012)
Bobby Dollar, an angel who has taken part in the long battle between Heaven and Hell, must figure out why there are suddenly an unprecedented number of souls missing from both sides and who summoned a Babylonian demon to kill him.